Technology 2000 - Evans, Peter (New York, N.Y. : Facts on File, 1985)
Examines some possible developments in technology and their effect on society in the areas of work, leisure, health, education, communication, transportations, and further exploration and use of outer space.
Spine title: Technology.
Series statement from jacket.
Includes index.
Keywords: Technology -- Juvenile literature; Technology